Hooked on Data Videos: Assessing the Effect of Animation and Pictographs on Viewer Engagement - Amini, Fereshteh; Henry Riche, Nathalie; Lee, Bongshin; Leboe-McGowan, Jason; Irani, Pourang (AVI '18 Proceedings of the 2018 International Conference on Advanced Visual Interfaces, 2018)
Pictographic representations and animation techniques are commonly incorporated into narrative visualizations such as data videos. General belief is that these techniques may enhance the viewer experience, thus appealing to a broad audience and enticing the viewer to consume the entire video. However, no study has formally assessed the effect of these techniques on data insight communication and viewer engagement. In this paper, we first propose a scale-based questionnaire covering five factors of viewer engagement we identified from multiple application domains such as game design and marketing. We then validate this questionnaire through a crowdsourcing study on Amazon’s Mechanical Turk to assess the effect of animation and pictographs in data videos. Our results reveal that each technique has an effect on viewer engagement, impacting different factors. In addition, insights from these studies lead to design considerations for authoring engaging data videos.